Il problema dell’egemonia nell’interpretazione gramsciana di Nicola Badaloni - Basile, Luca (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2020)
This paper aims at retracing Nicola Badaloni's interpretation of Gramsci’s thought. We will try to show that, starting from an approach that can be described as “historicist”, Badaloni has gradually changed his reading, up to a wholly different position, characterized by the use of categories that are quite unrelated to Gramsci’s thinking. Badaloni ends up supporting a position that lies at the crossroads between the subjectivism typical of Western Marxism and scientism. Badaloni Nicola; Gramsci Antonio; Hegemony; Western Marxism; Scientism, Praxis.